Application of HPTLC in Standardization of Homoeopathic Mother Tincture Andrographis paniculata and Its Comparison with Market Products - SHANBHAG, D.; JAYARAMAN, SUNITA (Asian Journal of Chemistry, 2010)
A simple and accurate HPTLC method has been developed for the quantification of andrographolide and fingerprinting of the in-house mother tincture considered here to be a standard with that of different marketed samples available from manufacturers of homoeopathic medicines in India. This HPTLC method was quantitatively evaluated in terms of stability, repeatability, accuracy and calibration providing the utility in the analysis of the mother tincture.